Early Clinical and Radiographic Outcomes of Combined Hip Arthroscopy and Periacetabular Osteotomy. Issue 7 (29th July 2014) - Ross, James R.; Keith, Angela; Pashos, Gail Elizabeth; Duncan, Stephen; Schoenecker, Perry; Clohisy, John C.
Objectives: Modern treatment of hip dysplasia has focused on the correction of the structural deformity with the periacetabular osteotomy (PAO), which addresses the deformity by redirecting the acetabulum into an improved mechanical position. Hip arthroscopy has allowed an increased awareness of the intra-articular pathology associated with acetabular dysplasia. The combination of hip arthroscopy with periacetabular osteotomy allows for treatment of both intra-articular and structural abnormalities associated with hip dysplasia. However, there is limited information regarding this combined approach for treating symptomatic acetabular dysplasia. The purpose of this study was to report the early clinical and radiographic outcomes of combining hip arthroscopy with PAO compared to PAO alone. Methods: We retrospectively reviewed 48 hips (46 patients) who underwent hip arthroscopy combined with periacetabular osteotomy (HS-PAO) and compared them to a control group of 62 hips (54 patients) who underwent PAO alone. The minimum clinical follow-up of the HS-PAO group was 12 months (mean, 31.4 months; range, 12-79 months), which was not significantly different from the control group (mean, 28.7 months; range, 12-71 months; p = 0.39). Pre-operative and post-operative standardized radiographs were analyzed for findings of acetabular dysplasia, including lateral center-edge angle (LCEA), acetabular inclination, anterior-center edge angle (ACEA), and Tönnis osteoarthritis grade. Clinical outcomes were evaluated with the UCLA activity score, modified Harris hip score (mHHS), short form-12 (SF-12), and the Western Ontario and McMaster Universities Arthritis Index (WOMAC). Perioperative complications were graded and compared between the two groups. Results: The mean age of the patients in the HS-PAO group was 28.0 years (range, 12 to 47 years), which was not significantly different from the control group (p = 0.35). Forty-four hips (91.7%) were in female patients, and 58% were right-sided. There was significant change in the mean LCEA (15.1° vs. 29.7° ; p < 0.0001), acetabular inclination (15.0° vs. 2.8° ; p < 0.0001), and ACEA (16.5° vs. 33.7° ; p <0.0001). The preoperative UCLA, mHHS, and SF-12 scores were not significantly different between groups. The HS-PAO group had a significantly higher pre-operative total WOMAC score (40.6 vs. 30.8; p = 0.03). The HS-PAO and control groups both saw significant improvement in the mHHS (23.5 vs. 21.3), SF-12 physical (7.5 vs. 9.1) scores, which were not significantly different from each other (all p-values > 0.3). The PAO-HS group, however, experienced a 0.9 improvement in the UCLA score, which was significantly different from the control group (-0.2; p = 0.03). The PAO-HS group also experienced a significantly greater improvement in the total WOMAC score (27.0 vs. 17.8; p = 0.03). There were no significant differences in the complication between the groups. Within the PAO-HS group, there were 16 lateral femoral cutaneous nerve palsies (33.3%) that resolved with outpatient management. There was 1 posterior column fracture that was treated nonoperatively. Conclusion: At short-term follow-up, hip arthroscopy with PAO shows equal to improved clinical outcomes with similar radiographic changes when compared to PAO alone without an increase in major complications. Patients that underwent hip arthroscopy combined with PAO also experienced a larger increase in activity level when compared to PAO alone.